From expert to advanced clinical practitioner and beyond. (10th June 2021) - Mortimore, Gerri; Reynolds, Julie; Forman, Dawn; Brannigan, Chris; Mitchell, Kathryn
Abstract : This article considers the potential development of advanced clinical practitioners (ACPs) and consultant practitioners, beyond the 'expert' status as defined by Pat Benner in 1984. The suggested Derby Model: 7 Levels of Practice Advancement, adapted from Benner's From Novice to Expert, recognises Health Education England's four pillars of advanced practice and how they can be implemented and enhanced within these senior roles, and what that means in a 21st century healthcare system.